Comparative clinical-related outcomes of Chinese patent medicines for cardiac hypertrophy: A systematic review and network meta-analysis of randomized clinical trials - Zhang, Tianqi; Xu, Haoyang; Zhen, Dong; Fu, Danni; Zhao, Ming; Wei, Chengxi; Bai, Xue (Frontiers in Pharmacology, 2023)
Background: Persistent pathological cardiac hypertrophy was associated with an increased risk of heart failure, even sudden death. Multiple kinds of Chinese patent medicines (CPMs) had gained attention as alternative and complementary remedies, due to their high efficiency and low side effects. However, effects of CPMs related treatment regimens of cardiac hypertrophy had not been systematically evaluated. Aim: The objective of this study was to estimate and compare the effectiveness of different mechanisms of CPMs for improvement of different clinical outcome including clinical efficacy and Echocardiographic Indices etc in the treatment of cardiac hypertrophy patents. Methods: A network meta-analysis was conducted regarding CPMs related randomized controlled trials (RCTs) published between 2012 and 2022 involving cardiac hypertrophy patients from 4 foreign databases and 4 Chinese databases. The outcomes concerned efficacy and related indicators including Echocardiographic Indices, Cardiac Biomarkers, and Functional Exercise Capacity which were evaluated as odds ratios, mean differences and 95% credible intervals. Network plots, league tables, surface under the cumulative ranking (SUCRA) and funnel plots were created for each outcome, and all analyses were conducted by Stata 16.0 software. Results: 25 RCTs were enrolled involving 2395 patients into NMA. The results from existing evidence indicated that “Blood-Activating and Stasis-Removing Chinese Patent Medicine (BASR-CPM) + Western Medicine (WM)” had good improvement in Clinical Efficacy (OR = 8.27; 95%CI = 0.97,70.73). Combined treatment regimen of “CPM with function of Qi-Replenishing, Blood-Activating and Stasis-Removing and WM” was an effective treatment regimen for Echocardiographic Indices like decreasing LVESD (SMD = -2.35; 95%CI = -3.09, -1.62) and LVMI (SMD = -1.73; 95%CI = -2.92, -0.54). Furthermore, “KWYR-CPM + WM” and “BASR-CPM” also had good improvement for Echocardiographic Indices of LVEDD (SMD = -1.84; 95%CI = -3.46, -0.22) and LVEF (SMD = 1.90; 95%CI = -0.46, -3.35) respectively. Conclusions: The study showed that “BASR-CPM+WM” may be the potential superior treatment regimen for improving clinical efficacy among cardiac hypertrophy patients. “QR&BASR-CPM+WM” might be the optimum selection for decreasing LVESD and LVMI. However, due to potential risk of bias and limited RCTs, further studies with larger sample and high-quality RCTs are needed to support these findings.